Benchmarking exercise using Data Envelopment Analysis, an application to irrigation water pricing - Giannoccaro G.; Berbel J.; Prosperi M.; Zanni G. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
Water management is subject to conflicting economic and environmental objectives and policy makers require a clear overview of the various outcomes of different water management options. In the present paper we propose a non-parametric benchmarking technique based on Data Envelopment Analysis (DEA), specifically developed to assess the relative efficiency of alternative water pricing policies. The result of the analysis is a ranking of pricing policies, aimed at supporting decision making process. An empirical study case was carried out in Southern of Italy (Apulia region), where irrigation is an important factor of strategic relevance for policy makers. Six different pricing methods were compared. According to the findings, the alternative pricing policies perform similarly in terms of technical efficiency. However, the results show that the alternatives rank differently for the technical efficiency and the ecological efficiency indicator. The ecological efficiency shows up to 10 percent of inefficiency. We conclude that efficiency may be a convenient method for ranking policy hypotheses in the case of absence of information on stated preferences on some outcomes, as well as some negative environmental impacts.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)